Best practice principles for AW&E providers (Australian Institute of Sport, 2020)
In August 2018, the Australian Government launched "Sport 2030" with a clear objective - to ensure Australia is the most active and healthy nation, known for its integrity and sporting success. The National High Performance Sport Strategy (NHPSS) was developed in support of one of the identified priorities in Sport 2030, namely the achievement of sporting excellence.Athlete Wellbeing and Engagement (AW&E) is widely recognised as essential to the fostering and retentionof talent in the Australian high performance (HP) sport system. In encompassing the mental, physical, and emotional health of HP athletes, AW&E supports sustained excellence in high performance as well as success in all other major aspects of life.The increased prominence of AW&E in the HP system requires continued progress to be based on a foundation of shared and mutually agreed understandings. For this reason the Australian Institute of Sport (AIS), in collaboration with its National Institute Network (NIN) partners, National Sporting Organisations (NSOs), and professional sporting bodies, has developed Best Practice Principles for AW&E Providers. These Best Practice Principles will develop as AW&E continues to evolve, and will be revised from time to time to remain contemporary and relevant to the changing HP landscape.